(untitled) (Global Conference on Medical and Health Sciences, 2026)
This study investigated the diagnostic value of Klotho protein and vitamin D in the early detection of renal dysfunction in patients with hypertension. Serum levels of cystatin-C, Klotho protein, vitamin D, and parathyroid hormone were evaluated in 169 hypertensive patients and 23 healthy volunteers. Correlations between these biomarkers across different stages of hypertension were established. The addition of vitamin D supplementation (Detrimax 5000 IU) to standard therapy demonstrated a statistically significant positive effect on hemodynamic parameters and markers of renal dysfunction.